Enhancing nitrogen use efficiency in agriculture by integrating agronomic practices and genetic advances - Ali, Aamir; Jabeen, Nida; Farruhbek, Rasulov; Chachar, Zaid; Laghari, Azhar Ali; Chachar, Sadaruddin; Ahmed, Nazir; Ahmed, Shoaib; Yang, Zhenping (Frontiers in Plant Science, 2025)
Nitrogen is a critical nutrient for plant growth and productivity, but inefficiencies in its use in agriculture present both economic and environmental challenges. Enhancing nitrogen use efficiency (NUE) is essential for promoting sustainable crop production and mitigating the negative impacts of nitrogen loss, such as water pollution and greenhouse gas emissions. This review discusses various strategies aimed at improving NUE, with a focus on agronomic practices, genetic advancements, and integrated management approaches. Traditional agronomic methods, including split nitrogen application and the use of controlled-release fertilizers, are explored alongside precision agriculture techniques, which enable real-time adjustments to nitrogen application based on crop and soil conditions. Advances in genetics and biotechnology, such as conventional breeding, genetic modification, and genome editing, have contributed to the development of crop varieties with improved nitrogen uptake and assimilation. Additionally, the role of beneficial microbes, including nitrogen-fixing bacteria and mycorrhizal fungi, is highlighted as a natural means of enhancing nitrogen availability and reducing reliance on synthetic fertilizers. The review further emphasizes sustainable practices such as legume-based crop rotations, continuous cover cropping, and organic fertilization, which contribute to soil nitrogen enrichment and overall soil health. By combining these agronomic, genetic, and microbial strategies, a holistic nitrogen management approach can be achieved, maximizing crop yields while minimizing environmental impacts. This integrated strategy supports the development of resilient and sustainable agricultural systems, promoting long-term soil fertility and productivity.